2020
DOI: 10.1186/s12969-020-00436-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Henoch-Schönlein Purpura with bullous rash and pulmonary nodules

Abstract: Background: Henoch-Schönlein purpura (HSP) is the most common vasculitis of childhood. It has a characteristic rash described as palpable purpura that most frequently affects the distal lower extremities and buttocks. HSP rarely presents with bullous rash nor pulmonary nodules. Case presentation: We present a novel case of a 12-years-old female with recurrent pediatric HSP with a combination of the rare manifestations of bullous rash and pulmonary nodules. She initially presented with the bullous rash, chest p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In a recent review, only 23 paediatric cases were reported in the literature and almost all had renal involvement 40 . The disease is potentially fatal and a standard therapy is lacking 40,41 . A combination of steroids and immunosuppressants (cyclophosphamide or azathioprine) has been used in previous reports 40,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, only 23 paediatric cases were reported in the literature and almost all had renal involvement 40 . The disease is potentially fatal and a standard therapy is lacking 40,41 . A combination of steroids and immunosuppressants (cyclophosphamide or azathioprine) has been used in previous reports 40,42 .…”
Section: Discussionmentioning
confidence: 99%
“…40 The disease is potentially fatal and a standard therapy is lacking. 40,41 A combination of steroids and immunosuppressants (cyclophosphamide or azathioprine) has been used in previous reports. 40,42 In our experience, our patient had a resolution of proteinuria after 6 weeks of initiating cyclosporin therapy, without any late sequelae.…”
Section: Iga Vasculitis and Risk Factors For Renal Involvement In Patients Agedmentioning
confidence: 99%